THE ANALYSIS OF ENGLISH-INDONESIAN TRANSLATION AT WELCOME ON BOARD SECTION ON GARUDA MAGAZINE - Kuswardani, Yuli (English Teaching Journal, 2014)
The main aim of this study is to explain the quality of translation of Garuda Magazine from English into Indonesian. The analysis concerns on accuracy, clarity/clearness and naturalness of translation of Garuda Magazine from English into Indonesian. The research method uses qualitative descriptive and the type of research is content analysis. This research takes the section âWelcome on Boardâ page 12 on Garuda Magazine November 2008 edition as source of data. The result of the research shows that 3 data (15,79%) are less accurate and 84,21% or 16 sentences are accurate; 3 data (15,79 %) are less clear and 84,21% or 16 sentences are clear; 5,26 % or 1 sentence is unnatural, 36,84 % or 7 sentences are less natural and 57,90 % or 11 sentences are natural.